Morphological study of the oral denticles of the porbeagle shark Lamna nasus - Poscai, Aline N. [UNESP]; Silva, João Paulo C. B. da; Casas, André Luis S.; Lenktaitis, Phillip; Gadig, Otto B. F. [UNESP] (Wiley, 2022)
Oral denticles of sharks are composed by a crown, dentine covered by a layer of enameloid and pulp cavity, the same structure of the dermal denticles found across the body surface of most elasmobranchs. In addition, oral papillae and taste buds are distributed among denticles within the oropharyngeal cavity, playing a fundamental role for tasting as part of the chemosensory system of fishes. Scanning electron microscopy (SEM) has been employed as an important tool for the study of dermal denticles and other structures, as well as histology and more recently computed tomography (CT) scan analysis. Herein, the authors used two methods for the study of the morphology of the oropharyngeal cavity of Lamna nasus (Lamniformes), an oceanic and pelagic shark: SEM and CT scan. The general morphology of oral denticles studied herein is related to abrasion strength as they are diamond-shaped, lack lateral cusps and have less pronounced ridges. In addition, smooth ridges and broad rounded denticles could be related to prevent abrasion during food consumption and manipulation. Oral papillae had a round shape and were observed only under SEM. The densities of papillae were estimated in 100 per cm2, whereas denticles were 1760 and 1230 cm2 over the dorsal and ventral regions, respectively. The high numbers of denticles are inversely proportional to papillae density; denticles seem to restrict papillae distribution. Regarding the differences between methodologies, under SEM, only the crown was visualized, as well the papillae, allowing the estimation of size and density of both structures. Nonetheless, under CT scan, the whole components of denticles were clearly visualized: different views of the crown, peduncle, basal plate, and pulp cavity. On the contrary, oral papillae were not visualized under CT due to the tissue preparation. Furthermore, both methods are complementary and were important to extract as much information as possible from denticles and papillae.
Keywords: CT scan; Lamnidae; oropharyngeal cavity; scanning electron microscopy